Low‐power SOI CMOS antenna switch driver circuit with RF leakage suppression and fast switching time - I.‐Y. Lee; D. Im (Electronics Letters)
A low‐power antenna switch driver circuit with RF leakage suppression and fast switching time is implemented in a 0.25 μm silicon‐on‐insulator (SOI) CMOS process. It is composed of a three‐stage current starved ring oscillator with a clock buffer, a charge pump and a latch‐based three‐state logic driver. The negative voltage from the charge pump is fed into the latch‐based three‐state logic driver, and it generates three states of logic level (+VDD, GND and −VDD) according to the decoder signal without any reliability issue. In addition, the proposed three‐state logic driver with an optimal negative resistance value reduces the amount of the RF leakage coupling into the charge pump while maintaining its switching time fast. In the measurement, the designed switch driver circuit shows <0.1 V of voltage loss under 150 μA of current consumption. A single‐pole double‐throw antenna switch employing the proposed switch driver circuit is implemented in a 0.25 μm SOI CMOS process. The measurement shows higher than +38 dBm of 1 dB compression point (P1dB) and 140 ns of switching time while allowing <0.5 dB of insertion loss and >30 dB of isolation over 100 MHz to 3 GHz frequency range.